Outcomes of Policy-Oriented Research in the CGIAR - Renkow, M. (CGIAR Independent Science and Partnership Council, 2018)
Policy-oriented research—defined as research aimed at identifying new or improved policies, regulations, or institutions (or their management) that enhance economic, social, and environmental welfare (Raitzer and Ryan, 2008)—is an important and growing part of CGIAR portfolio. Its importance is reflected in CGIAR’s Strategy and Results Framework as a cross-cutting outcome on “improving the enabling environment” through better policies and institutions.